Health Associations of Drug-Involved and Criminal-Justice-Involved Adults in the United States. (March 2014) - Vaughn, Michael G.; Salas-wright, Christopher P.; Delisi, Matt; Piquero, Alex R.
A burgeoning criminological literature has identified important intersections between public health, crime, and antisocial behavior. This study is based on public-use data collected between 2006 and 2010 as part of the National Survey on Drug Use and Health (NSDUH) and an analytical sample of men ( N = 84, 054) and women ( N = 95, 308) between the ages of 18 and 64. Latent class analysis (LCA) identified three classes: a large normative group, a small drug-involved group, and a criminal-justice-involved group. Chronic health conditions that are more closely associated with longer term medical problems and perhaps cumulative stress such as heart disease and diabetes are not linked to criminal-justice-system-involved or drug-involved offenders. Medical problems that are more closely related to an antisocial lifestyle such as sexually transmitted diseases, pancreatitis, and hepatitis were found to be more prevalent among antisocial subgroups in this sample.